OCCUPATIONAL SAFETY AND HEALTH (OSH) MANAGEMENT PRACTICES OF BUILDING CONTRACTORS IN JOHOR, MALAYSIA - KHASNIMAN, FATIN NURFAZIRA; ABAS, NOR HASLINDA; ISMAIL, SUSHILAWATI; RAHMAT, MUHAMAD HANAFI; HASMORI, MUHAMMAD FIKRI (umt, 2023)
: It is believed that some building construction contractors are less aware of the safety and health aspects and are more likely to pursue profits over the safety and health of workers and people living near the construction site. Therefore, this study aims to investigate the implementation of safety and health practices by building contractors in Johor, Malaysia. This study employs a survey method distributing survey instruments to G6 and G7 contractors in Johor. Through this method, respondents need to choose which practices they had implemented at their company, give opinions on the factors that hinder the implementation such practices, and propose solutions to overcome those problems. Through this survey, the level of implementation of safety and health management practices among contractors was obtained. This study has also helped provide a better understanding of the current safety and health management practices implemented by contractors in the state and will provide information on the barriers to the implementation of safety and health management practices as well as solutions to problems faced by contractors in implementing those best practices.